(3GdcGaj aj Gdabg GdMfHdjs - (3GdbQTj, GdebOSj, GdLnqeGYjdj, Ke GdOeTbj, GHf bOGeI, YHO Gddg Hf eMeO Hf bOGeI, (B620 (3g`s
(3ChdgG (B:s
(3hGHJOGAg HYO GdHSedI heG Jhajbj EdG HGddg cJGH GdYJb (B: (3hgh bQHg efOhH EdjgG HOdjd eG Qhi CHh gQjQI bGd bGd QShd Udi Gddg Ydjg hSde ef CYJb QbHI eDefI CYJb Gddg Hcd CQH efg CQHG efg ef GdfGQs
(3BNQgG (B:s
(3hJfJgj gPg GdfSNI YfO bhdg aj cJGH GdOYGhi hdh GOYi GdOGQ dg hdCLHfj de jfJRY GdMGce fUjH GdCLfHj ef GdefcQ dCf GdTQjc jfhH Yf faSgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 67s
(3eYLe GdeDdajf (B2 / 227s
(3cTa GdXfhf (B2 / 1387s
(3TPQGJ GdPgH (B5 / 88s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs